PENGARUH SUBSTITUSI TEPUNG SORGUM DAN TEPUNG KACANG TANAH PADA PEMBUATAN SNACK BAR - Bhie, Maria Trivania; Sine, Juni Gressilda Louisa (Poltekkes Kemenkes Kupang, 2025)
The most dangerous food problem facing the world today is protein energy deficiency (KEP). Considering that children under five years of age often experience disorders related to lack of protein and energy, KEP refers to children who experience malnutrition due to low daily energy and protein intake or due to certain diseases. Snack bars are emergency food in the form of solid sticks that are rich in important nutrients, protein and calories that the body needs. The aim of this study was to evaluate the nutritional content and level of preference for snack bars made with substitute ingredients for peanuts and sorghum flour. This research used a completely randomized design (CRD) and three substitution treatments of sorghum flour and peanut flour at P1 (40%:40), P2 (50%:30%), and P3 (60%:20%)—an experimental study. . methodology. Research findings show that treatments P1 to P3 on average fall into similar groups. However, the Tukey test was added after the ANOVA test results showed that there were real differences between the three treatments in color, texture, aroma and taste. P1 has the most nutritional value, with energy (1,362.12 grams), protein (45.17 grams), fat (77.5 grams), and carbohydrates (132.47 grams) making up the energy nutritional value. In summary, treatments P1 to P3 generally belong to the same group. Based on the results of nutritional value and acceptability tests, P2 is the recommended snack bar because it tastes the best.